The effect of training and competency on employees’ organizational commitment at PT. Bank Danamon in Ambon city - Ventje Jeffry Kuhuparuw; Sherly Ferdinandus (Universitas Hayam Wuruk Perbanas, 2014)
This study aims to identify and analyze training, competency, and organizational commitment; It also analyzes the effect of training on organizational commitment, the effect of competency on organizational commitment, the effect of training and compe- tency on organizational commitment at PT Bank Danamon in Ambon City. The method applied is a survey research method to 60 employees of PT Bank Danamon in Ambon. Technical analysis used to test the hypothesis is multiple linear regres- sion.The results indicate that training shows the effect of 89.5%, and competency of 13.0%. Since other factors also are predicted to affect the improvement of organiza- tional commitment in addition to training and competency, it is necessary to include the provision of motivation and clarity of career. From the point of view of the rela- tionship with the employees, both variables are considered as important parts. Leaders are also expected to actively involve in the implementation of the tasks so that interac- tion between leaders and subordinates can be interwined, and this cumulatively helps leaders know the problems faced by employees. Thus, the employees would feel cared for and this subsequently has impact on loyalty to the company or higher commitment.